A comparative assessment of ASM4 rockfall barrier modelling. (15th January 2022) - Boulaud, R.; Douthe, C.
Abstract: One key element of flexible rockfall barriers is the net which intercepts the block trajectory. The ASM4 ring net is one of the widely spread net technology for medium to high energy impacts. The accurate modelling of its mechanical behaviour has thus been the aim of many research programs, most of which use the discrete elements method and tension members with material non-linearities. This paper proposes hence a comparison of the three main families of models: linear spring models, tensile ring models and flexural ring models. First, homogenisation techniques are used to characterise intrinsic properties at local scale. Then, the question of the experimental identification of these properties is addressed. Afterwards, the relevance of the identified behaviour is investigated through two case studies. The first one consists in a simple hyperbolic paraboloid structure which has a closed form solution involving large displacements. The second one is based on an experiment on a reduced scale barrier with centred impact and extend the comparison to various kind of data and loading cases. The conclusion presents the main results of the various comparisons, it gives insight on the features that each model can capture and provides some guidelines for designers at early stage design. Highlights: The present study embraces all scales of the ASM4 ring net from local modelling to the global barrier. Comparisons of models are conducted for small and large displacements, for problems with closed form solutions as well as experimental data. Identification of model parameters on physical experiments is also addressed. A novel type of modelling based on a bent ring element is proposed and validated.